A deep learning model for novel systemic biomarkers in photographs of the external eye: a retrospective study - Boris Babenko; Ilana Traynis; Christina Chen; Preeti Singh; Akib Uddin; Jorge Cuadros; Lauren P. Daskivich; April Y. Maa; Kim Ramasamy; Eugene Yu‐Chuan Kang; Yossi Matias; Greg S. Corrado; et al. (2023)
Photographs of the external eye were recently shown to reveal signs of diabetic retinal disease and elevated glycated haemoglobin. This study aimed to test the hypothesis that external eye photographs contain information about additional systemic medical conditions.